Wilting rationalism in technical decision making - ICASP14; Heroes, Yves; Maes, Marc (My University, 2023)
Decision makers in diverse engineering disciplines, ranging from technical risk analysis and design to the development of risk-informed policies that impact on technology and society, benefit from the existence of a solid and well-respected theory for principled decision making. The requirement of ﾓrationalityﾔ when applying the tools/techniques within the decision making framework, is fundamental yet largely taken for granted. New age thinking has shifted many of the distinctive features of ﾓrationalﾔ decision making. This paper identifies a set of key ﾓmodernistic attitudesﾔ that have recently emerged from shifting value systems and changing socio-economic preferences. It provides case studies and examples of how such attitudes lead to poor decisions. The paper also outlines a Bayesian framework to potentially account for and/or rectify specific attitudes. Rational and systematic thinking is becoming a neglected victim to many ﾓmodernistic attitudesﾔ. To start with, the attitude of ultracrepidarianism suggests that it is OK to sacrifice/ignore science and research in favour of strongly felt opinion. Similarly, the sociological trend of juvenilization suggests there is added value in making cool and even entertaining decisions. Financialization, market-driven decisions, and other forms of ﾓsponsoredﾔ preference promotion are key drivers in shifting attitudes in todayﾒs technical decision making. The gradual rise of a precautionary culture that started almost 50 years ago has, in specific technological areas, germinated attitudes ranging from short-term (bounded) rationalism to excessive caution and has triggered a reactionary counter stream of largely irrational attitudes such as recklessness with facts and figures, and presumption with regards to the feasibility of technical solutions. The paper stresses that we need a fresh re-evaluation of rationalism in the context of decision making. The emphasis has shifted away from the paradigm ethical contrast between rational decision making versus irrational decision making with a whole series of new-wave attitudes re-shaping thinking, methodology, and analysis. In the paper we also outline a Bayesian framework for capturing the effect of specific ﾓattitudesﾔ in decision making. This framework is based on the calibration of posterior information about such attitudes based on ﾓstatedﾔ decisions in a multi-decision-maker context. Such analysis can provoke insight into the assessment of the ﾓqualityﾔ of decisions with respect to key attitudes; it may help re-assess shaky decisions and offer resolution between conflicting decisions. However, ﾓrationalityﾔ remains a rather vague principle, but one that cannot be bypassed as it plays an essential role in quality decision making.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED